Robotic actuator control through eye-tracking camera to assist people with physical limitations - Ferraz, Ariéle T.; Marcato, André L. M.; Schettino, Vinícius B.; Melo, Aurélio G. (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2023: Anais do XV Simpósio Brasileiro de Robótica e XX Simpósio Latino Americano de Robótica, 2023)
Technological advancements have been allowing the development of increasingly advanced assistive methods. These assistive technologies have the potential to increase comfort for people with physical disabilities. Within this context, developing methods capable of identifying user commands and controlling robotic actuators is important to the field. This work presents a methodology to track eye-movements for identifying user pick-and-place commands, using a simple webcam and a robotic arm. Simulation results are also presented using the proposed methodology. From these results, it is possible to verify that the method is viable for further experimentation in a real environment.